PENGARUH PENGHINDARAN PAJAK JANGKA PANJANG PADA NILAI PERUSAHAAN DENGAN TRANSPARANSI INFORMASI SEBAGAI VARIABEL PEMODERASI - Partha, I Gede Angga; Noviari, Naniek (E-Jurnal Akuntansi; Vol 14 No 3 (2016), 2016)
This study aimed to examine the effect of long-term tax evasion in the value of the company with the information transparency as moderating variables. The sample was non-sector financial services company listed on the Indonesia Stock Exchange in 2010-2014, using purposive sampling method. The Company elected to a sample of 70 companies observations. The data analysis technique used is a simple regression analysis and test interactions (moderated regression analysis). Long run cash ETR is used to measure the variable tax evasion. Tobins Q ratio is used to measure the variable value of the company, and the completeness of voluntary disclosure index is used to measure the variable transparency of information. The results provide evidence that companies that perform long-term tax evasion does not significantly influence the value of the company, but the transparency of information can moderate the effects of long-term tax evasion so that companies that tax evasion will be a positive effect on the value of the company if the transparency of company information also good.
Keywords: Taxation, Corporate Values, Transparency Information